Engaged parenting in the era of information overload and parent autonomy.Psychopedagogical reflections - Lidia Wisniewska-Nogaj (Studia z Teorii Wychowania)
Parenting can be considered one of the most difficult challenges, affecting the implementation of developmental tasks for both the child and the parent. Engaged parenting has been promoted for many years, requiring the parent to actively participate in the child's everyday life and development. It lasts practically throughout the child's life and requires not only attentiveness and responsiveness, but also expanding one's own knowledge and skills. Nowadays, the Internet is becoming the basic source of information about child development. This raises a number of difficulties, e.g. related to the quality of information, access to it, its reliability or excessive quantity. Access to the Internet can become a source of both support and a sense of information overload. This affects the parent's well-being, including the fulfillment of his or her needs. The aim of this article is to reflect on how engaged parenting in the era of information overload affects the fulfillment of the need for autonomy.